Molecular subtyping of breast carcinomas in urban and rural Indian population – A cross-sectional study. - Sahu, Ajaya Kumar; Behera, Chandra Sekhar; Samal, Swaraj Sambit; Mohanty, Sujit Kumar (Student's Journal of Health Research Africa, 2025)
Background Consequently, one crucial aspect for the treatment profile of breast cancer is the classification of breast cancer into pertinent molecular subgroups. Breast cancer is divided into four primary clinical subtypes based on gene expression profiles, receptor status, and proliferative status. There hasn't been much research done on how common these molecular subtypes are among Indian people. Objectives The purpose of conducting this analysis was to evaluate the molecular subtyping of breast cancer in Indians living in both urban and rural areas. Materials and Methods It was a prospective, observational study. The study was carried out in SCB Medical College & Hospital, Odisha, India. The study was conducted for two years, that is, from January 2023 to April 2025. In all, 150 patients were enrolled. Study participants included all females with breast cancer. Results With 83 (55.3%) patients older than 50, the mean age at diagnosis was skewed toward older patients. Metastases from lymph nodes were found in 89 patients, or 59.3%. In 32 (21.3%) of the cases, distant metastases were discovered at the time of initial presentation. Of the population, 24 (16.0%) had luminal A-like tumors. Conclusion This study uses immunohistochemistry surrogate markers to show the distribution of subtypes that are molecular in breast cancer in an Indian population living in both urban and rural areas. The majority of patients come with high-grade tumors and substantial nodal involvement, and the results show a preponderance of aggressive subtypes, including TNBC and Luminal B-like cancers. Recommendation Routine molecular subtyping using immunohistochemistry should be incorporated into the diagnostic evaluation of all invasive breast cancer cases to guide treatment decisions effectively.